Chemical-genetic analysis of cyclin dependent kinase 2 function reveals an important role in cellular transformation by multiple oncogenic pathways - Horiuchi, Dai (National Academy of Sciences, 2012)
A family of conserved serine/threonine kinases known as cyclin-dependent kinases (CDKs) drives orderly cell cycle progression in mammalian cells. Prior studies have suggested that CDK2 regulates S-phase entry and progression, and frequently shows increased activity in a wide spectrum of human tumors. Genetic KO/knockdown approaches, however, have suggested that lack of CDK2 protein does not prevent cellular proliferation, both during somatic development in mice as well as in human cancer cell lines. Here, we use an alternative, chemical-genetic approach to achieve specific inhibition of CDK2 kinase activity in cells. We directly compare small-molecule inhibition of CDK2 kinase activity with siRNA knockdown and show that small-molecule inhibition results in marked defects in proliferation of nontransformed cells, whereas siRNA knockdown does not, highlighting the differences between these two approaches. In addition, CDK2 inhibition drastically diminishes anchorage-independent growth of human cancer cells and cells transformed with various oncogenes. Our results establish that CDK2 activity is necessary for normal mammalian cell cycle progression and suggest that it might be a useful therapeutic target for treating cancer.